2004
DOI: 10.1158/1078-0432.ccr-1107-03
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-Dependent Cytotoxic Interaction between Epidoxorubicin and Gemcitabine in Human Bladder Cancer Cells in Vitro

Abstract: Purpose: The aim of the study was to evaluate the activity of epidoxorubicin (EPI) and gemcitabine (GEM) and to define the most effective schedule in human bladder cancer cells.Experimental Design: The study was performed on HT1376 and MCR cell lines. Cells were exposed for 1 and 24 h to drugs used in different schemes. Cytotoxic activity was evaluated by the sulforhodamine B assay, potential clinical activity was estimated by relative antitumor activity, and the type of drug interaction was assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Previous work on the AGS cell line using the same three chemotherapeutic agents and exposure times identified similar LD 50 concentrations of each agent, 5-FU 10 mg ml À1 , cisplatin 10 mg ml À1 and epirubicin 0.25 mg ml À1 (Couper and Park, 2003). In common with previous studies, exposure to epirubicin and cisplatin induced dose-dependent G 1 (LD 10 ) and G 2 (LD 50 ) cell cycle arrest Sorenson et al, 1990;Shapiro et al, 1998;Zoli et al, 2004). 5-FU exposure resulted in a build up of cells in S phase (LD 10 ) and G 1 (LD 50 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous work on the AGS cell line using the same three chemotherapeutic agents and exposure times identified similar LD 50 concentrations of each agent, 5-FU 10 mg ml À1 , cisplatin 10 mg ml À1 and epirubicin 0.25 mg ml À1 (Couper and Park, 2003). In common with previous studies, exposure to epirubicin and cisplatin induced dose-dependent G 1 (LD 10 ) and G 2 (LD 50 ) cell cycle arrest Sorenson et al, 1990;Shapiro et al, 1998;Zoli et al, 2004). 5-FU exposure resulted in a build up of cells in S phase (LD 10 ) and G 1 (LD 50 ).…”
Section: Discussionsupporting
confidence: 84%
“…5-FU exposure resulted in a build up of cells in S phase (LD 10 ) and G 1 (LD 50 ). Epirubicin, an anthracycline derivative of doxorubicin, exerts its anti-tumour effects via its action as a DNA intercalating agent and as an inhibitor of topoisomerase II (Cersosimo and Hong, 1986;Bartkowiak et al, 1992;Zoli et al, 2004). The arrest of AGS cells at higher concentrations of epirubicin may be related to peak activity of topoisomerases occurring during the G 2 phase (Chow and Ross, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary end points were time to recurrence, progression and overall tolerability. 37-h doubling time (obtained from American Type Culture Collection, Rockville, MD, USA) and a cell line (MCR) established in the Biological Laboratory of the Department of Medical Oncology in Forlì (Zoli et al, 2004), with a 48-h doubling time. Cells were maintained as a monolayer in culture medium (DMEM) supplemented with 10% FCS, 100 IU ml À1 penicillin, 100 mg ml À1 streptomycin and 2 mM L-glutamine and subcultured weekly.…”
mentioning
confidence: 99%
“…Authors communicate, in general, low levels of toxicity, with stomatitis greater than grade 2 in 14 -22% of patients and grade 4 neutropenia in 14 -21% (Pérez-Manga et al, 2000;Gómez et al, 2001;Yang et al, 2002). Exposure to 4-epidoxorubicin followed by gemcitabine proved to be synergistic in cancer cell lines grown in vitro, with a 65% increase in DNA damage when compared with the reverse sequence or simultaneous administration (Zoli et al, 2004). According to this finding, one might hypothesise that a higher DNA damage combined with a tissue-specific sensitivity could explain the poor mucosal and haematologic tolerance of our schedule.…”
Section: Discussionmentioning
confidence: 96%
“…In those studies, only gemcitabine was given on day 1, whereas on day 8 gemcitabine preceded TXT, a sequence that was synergistic in an osteosarcoma and a breast cancer cell line (Leu et al, 2004); however, in lung cancer cell lines, the opposite sequence was more effective (Zoli et al, 1999). Similarly, in vitro studies have shown that the effects of a combination of DXR and gemcitabine depend both on the sequence of administration and on the particular cell line studied (Chow et al, 2000;Zoli et al, 2004). The administration of gemcitabine followed by DXR, or the delivery of DXR on day 8, would perhaps offer a better therapeutic index than the present schedule, which cannot be recommended for further study.…”
Section: Discussionmentioning
confidence: 99%